Leaders’ mental health in times of crisis: work intensification, emotional demands and the moderating role of organizational support and self-efficacy - Wittmers, Anja; Maier, Günter W. (Frontiers in Psychology, 2023)
This article focuses on leaders’ specific demands in times of crisis and the role of personal and organizational resources regarding mental health. The COVID-19 pandemic has led to increased levels of responsibilities, particularly among leaders. To deepen the understanding about the resulting consequences in terms of leaders’ demands and resources, we conducted a mixed methods study with a sample of 60 leaders from lower and middle management. We hypothesized leaders’ work intensification and emotional demands to be related with higher irritation and exhaustion. Consistent with the Job-Demands-Resources Model and the Conservation of Resources Theory, we examined organizational instrumental support and occupational self-efficacy as possible moderators and assumed a buffering effect on mental illness. Our quantitative results indicated organizational instrumental support as a moderator for the relation of work intensification and mental illness. In terms of self-efficacy and work intensification, the results contradicted our expectations. For emotional demands, only the main effects could be found. In the qualitative part of our study, we found evidence for the importance of work intensification, emotional demands and organizational instrumental support in the leaders’ everyday experience and gained a deeper understanding of the constructs’ nature by means of examples. The integration of our quantitative and qualitative results has important and concrete implications for organizations how to support leaders in times of crisis and accelerated changes at work. This further underlines the necessity to consider leaders as an important target group of occupational health measures.